Targeting Right: Regional Variation In Food Crop Commercialization - Adong, Annet; Muhumuza, Tony; Mbowa, Swaibu (Economic Policy Research Centre, 2014)
Policy initiatives in Uganda have continuously laid emphasis on the need to transform the agriculture sector from subsistence farming to commercial. The country is also zoned into production regions for purposes of intensifying production based on comparative and competitive advantages. Focusing on the five major crops in Uganda, this policy brief provides evidence on the variation in regional food crop commercialization. It provides evidence in support of the commodity focused approach of targeting specific crops in selected agricultural zones. For example it shows that cassava is a viable crop enterprise for large scale commercial production in Northern Uganda while bananas is a viable enterprise for intensive production in Western Uganda. The policy brief emphasizes the need to pay attention to the agricultural zones in guiding interventions in crop farming.